The efficacy of a four-stage learning model incorporating ACODESA method and mind map in fostering students’ mathematical communication skills: A data report - Tong, Duong Huu; Uyen, Bui Phuong (Frontiers in Education, 2022)
Learning mathematics equips students with the necessary competencies, and mathematical communication abilities allow them to discuss and exchange mathematical ideas with others. Correspondingly, research is needed into ways to help students develop these skills. These data were collected from 87 students in grade 10 at An Nhon Tay High School in the Cu Chi neighborhood of Ho Chi Minh City, Vietnam. These students took part in a quasi-experimental study whose goal was to determine how a four-step learning model that included activities using the ACODESA method and mind maps affected the student’s ability to communicate mathematically. In the experimental group, students were taught using the learning mentioned above model, while those in the control group received traditional instruction. To determine the efficacy of this teaching strategy, a quasi-experiment that included a pre-test, a treatment, and a post-test was designed and carried out. The student’s development in mathematical and linguistic activities was evaluated using both quantitative and qualitative analyses of the data that was gathered. Data gathered may shed light on how effective the learning model is in helping high school students enhance their mathematical communication skills. Also, the pre-test and post-test items from the supplementary data files can be a starting point for creating new learning tasks to evaluate students’ mathematical communication abilities.